Biomechanical comparison of different screw-included angles in crossing screw fixation for transverse patellar fracture in level walking: a quasi-dynamic finite element study - Chih-Wei Chang; Yen-Nien Chen; Hung-Chih Chang; Chun-Ting Li (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background A minimally invasive technique with various screw configurations without open surgery is currently used for the fixation of transverse patellar fractures. Percutaneous crossing screw configuration has been reported to have a good bone union rate in patellar fractures. However, the difference in mechanical stability of the fractured patella between different screw-included angles has not been fully investigated. Hence, this study aims to compare the mechanical stability of parallel and crossing screw fixations with different screw-included angles for the fixation of transverse patellar fractures during level walking. Methods A finite element knee model containing a patella with a transverse fracture is created. Two headless compression screws with different angles (0°, 30°, 60°, and 90°) are used to fix the fracture. The loading conditions of the knee joint during level walking are used to compare the stability of the fractured patella with different fixation screw configurations. Results The results indicate that the maximum fracture gap opening distance increased with an increase in the included angle. Two parallel screws yield the smallest gap distance among all screw configurations. The maximum gap opening distances at the anterior leading edge of the fractured patella with two parallel screws and two screws having an included angle of 90° are 0.73 mm and 1.31 mm, respectively, at 15% walking cycle. Conclusions Based on these results, the superior performance of two parallel screws over crossing screw fixations in the fixation of transverse patellar fractures is established. Furthermore, the smaller the angle between the crossing screws, the better is the stability of the fractured patella.